T‐cell receptor diversity and allergen sensitivity in childhood asthma and atopic dermatitis - Chen, Pei‐Ling; Hung, Shuen‐Iu; Chung, Wen‐Hung; Chen, Chun‐Bing; Kuo, Chieh‐Ni; Lin, Yin‐Ku; Chiu, Chih‐Yung (Pediatric allergy and immunology, 2024)
Background Childhood allergies of asthma and atopic dermatitis (AD) involve an overactive T‐cell immune response triggered by allergens. However, the impact of T‐cell receptor (TCR) repertoires on allergen sensitization and their role in mediating different phenotypes of asthma and AD in early childhood remains unclear. Methods A total of 78 children, comprising 26 with asthma alone, 26 with AD alone, and 26 healthy controls (HC), were enrolled. TCR repertoire profiles were determined using a unique molecular identifier system for next‐generation sequencing. Integrative analyses of their associations with allergen‐specific IgE levels and allergies were performed. Results The diversity in TCR alpha variable region (TRAV) genes of TCR repertoires and complementarity determining region 3 (CDR3) clonality in TRAV/TRBV (beta) genes were significantly higher in children with AD compared with those with asthma and HC (p < .05). Compared with HC, the expression of TRAV13‐1 and TRAV4 genes was significantly higher in both asthma and AD (p < .05), with a significant positive correlation with mite‐specific IgE levels (p < .01). In contrast, TRBV7‐9 gene expression was significantly lower in both asthma and AD (p < .01), with this gene showing a significant negative correlation with mite‐specific IgE levels (p < .01). Furthermore, significantly higher TRAV8‐3 gene expression, positively correlated with food‐specific IgE levels, was found in children with AD compared with those with asthma (p < .05). Conclusion Integrated TCR repertoires analysis provides clinical insights into the diverse TCR genes linked to antigen specificity, offering potential for precision immunotherapy in childhood allergies.